Developing and Validating a Web-Based Five-Tier DiagnosticInstrument to Identify Student Misconceptions on Temperature and Heat - Hanum, Azizah; Maison; Yusnaidar (Yayasan Nurul Yakin Bunga Tanjung, 2026)
This study aims to develop and validate a web-based five-tier isomorphic diagnostic instrument to identify students’ misconceptions on temperature and heat concepts in junior high school. This research employed a quantitative developmental approach, involving instrument development, construct validation, and descriptive analysis of students’ responses. The instrument consisted of nine multiple-choice items structured into five tiers and was validated using factor analysis (Principal Component Analysis), with all items showing factor loadings greater than 0.50. Reliability testing using Cronbach’s alpha yielded a coefficient of 0.745, indicating high internal consistency. A total of 101 eighth-grade students from SMP Negeri 12 Jambi participated in the study by completing the web-based diagnostic test. The results identified 13 types of misconceptions, with an average misconception rate of 12.56% across all tiers, indicating that although students’ overall misconceptions were relatively low, several fundamental concepts related to temperature and heat remained problematic. The most common misconception was that dividing an object divides its temperature, accounting for 36.6%. Compared to conventional one-tier or two-tier diagnostic tests, this five-tier isomorphic instrument provides more detailed diagnostic information by incorporating students’ reasoning and confidence levels. Therefore, this instrument contributes to science education research by providing a valid, reliable, and practical tool for diagnosing students’ conceptual understanding and supporting more effective instructional planning in physics.